2019
DOI: 10.4103/ipj.ipj_15_18
|View full text |Cite
|
Sign up to set email alerts
|

Rate and risk factors of nocturnal enuresis in school going children

Abstract: Purpose: The purpose is to find out the rate of nocturnal enuresis in school going children (5–12 years) and the risk factors associated with it. Materials and Methods: The parents of children aged between 5 and 12 years studying in two primary schools in Ahmedabad completed a self-administered semi-structured questionnaire comprising of enuresis, sociodemographic profiles, and risk factors. Children with enuresis and those without were compared on demographic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Most studies have revealed a positive parental history in about 36% of children. These children were 10.1 times more likely to have NE (15,16). In our study, the prevalence of parental history was 18.7% and the odds ratio of enuresis was 15.03 times higher if both parents had a positive history of NE.…”
Section: Discussionsupporting
confidence: 40%
“…Most studies have revealed a positive parental history in about 36% of children. These children were 10.1 times more likely to have NE (15,16). In our study, the prevalence of parental history was 18.7% and the odds ratio of enuresis was 15.03 times higher if both parents had a positive history of NE.…”
Section: Discussionsupporting
confidence: 40%
“…The results of study by Alexander revealed 8.8% mothers with nocturnal enuresis and 0.7% with daytime urinary incontinence and 9.6% fathers had nocturnal enuresis and 0.3% daytime urinary incontinence. 4 Contradictory results were found in a study in Ethiopia the mothers of 55.13% (113) had the problem of enuresis while 16.59% (34) father, 17.07% (35) siblings, 10.24% (21) cousin and 0.97% (2) had enuretic relatives. In the current study 64% children had urinary infection.…”
Section: Resultsmentioning
confidence: 92%
“…3 The prevalence estimation of Nocturnal Enuresis was varied in different part of the country, one of the studies was conducted in Ahmedabad, Gujrat shoes prevalence rate was 11.13 % and more common in the male than female children. 4…”
Section: Introductionmentioning
confidence: 99%